A survey of combat athletes' rapid weight loss practices and evaluation of the relationship with concussion symptom recall - Uddin, N.; Waldron, M.; Patterson, S. D.; Winter, S.; Tallent, J. (Clinical Journal of Sport Medicine, 2022)
Objective: There is a high incidence of concussion and frequent utilization of rapid weight loss (RWL) methods among combat sport athletes, yet the apparent similarity in symptoms experienced as a result of a concussion or RWL has not been investigated. This study surveyed combat sports athletes to investigate the differences in symptom onset and recovery between combat sports and evaluated the relationships between concussion and RWL symptoms. Design: Cross-sectional study. Setting: Data were collected through an online survey. Participants: One hundred thirty-two (115 male athletes and 17 female athletes) combat sport athletes. Interventions: Modified Sport Concussion Assessment Tool (SCAT) symptom checklist and weight-cutting questionnaire. Main Outcome Measures: Survey items included combat sport discipline, weight loss, medical history, weight-cutting questionnaire, and concussion and weight-cutting symptom checklists. Results: Strong associations ( r s = 0.6-0.7, P < 0.05) were observed between concussion and RWL symptoms. The most frequently reported symptom resolution times were 24 to 48 hours for a weight cut (WC; 59%) and 3 to 5 days for a concussion (43%), with 60% to 70% of athletes reporting a deterioration and lengthening of concussion symptoms when undergoing a WC. Most of the athletes (65%) also reported at least one WC in their career to " not go according to plan ," resulting in a lack of energy (83%) and strength/power (70%). Conclusions: Rapid weight loss and concussion symptoms are strongly associated, with most of the athletes reporting a deterioration of concussion symptoms during a WC. The results indicate that concussion symptoms should be monitored alongside hydration status to avoid any compound effects of prior RWL on the interpretation of concussion assessments and to avoid potential misdiagnoses among combat athletes.